Wheel running during chronic nicotine exposure is protective against mecamylamine‐precipitated withdrawal and up‐regulates hippocampal α7 nACh receptors in mice. (22nd December 2017) - Keyworth, Helen; Georgiou, Polymnia; Zanos, Panos; Rueda, André Veloso; Chen, Ying; Kitchen, Ian; Camarini, Rosana; Cropley, Mark; Bailey, Alexis
Abstract : Background and Purpose: Evidence suggests that exercise decreases nicotine withdrawal symptoms in humans; however, the mechanisms mediating this effect are unclear. We investigated, in a mouse model, the effect of exercise intensity during chronic nicotine exposure on nicotine withdrawal severity, binding of α4β2*, α7 nicotinic acetylcholine (nAChR), μ‐opioid (μ receptors) and D2 dopamine receptors and on brain‐derived neurotrophic factor (BDNF) and plasma corticosterone levels. Experimental Approach: Male C57Bl/6J mice treated with nicotine (minipump, 24 mg·kg −1 ·day −1 ) or saline for 14 days underwent one of three concurrent exercise regimes: 24, 2 or 0 h·day −1 voluntary wheel running. Mecamylamine‐precipitated withdrawal symptoms were assessed on day 14. Quantitative autoradiography of α4β2*, α7 nAChRs, μ receptors and D2 receptor binding was performed in brain sections of these mice. Plasma corticosterone and brain BDNF levels were also measured. Key Results: Nicotine‐treated mice undertaking 2 or 24 h·day −1 wheel running displayed a significant reduction in withdrawal symptom severity compared with the sedentary group. Wheel running induced a significant up‐regulation of α7 nAChR binding in the CA2/3 area of the hippocampus of nicotine‐treated mice. Neither exercise nor nicotine treatment affected μ or D2 receptor binding or BDNF levels. Nicotine withdrawal increased plasma corticosterone levels and α4β2* nAChR binding, irrespective of exercise regimen. Conclusions and Implications: We demonstrated for the first time a profound effect of exercise on α7 nAChRs in nicotine‐dependent animals, irrespective of exercise intensity. These findings shed light onto the mechanism underlining the protective effect of exercise on the development of nicotine dependence. Linked Articles: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc